Simulating river discharge for Selangor River Basin - Azim Ashraf, Othman (2016)
In this study, Hydrologic Engineering Center – Hydrologic Modeling System (HECHMS) is used to determine the rainfall-runoff relationship of Selangor River Basin. Hence, this study aims to predict the streamflow in the ungauged catchment within the Selangor River using HEC-HMS model. HEC-HMS 4.1 is used in this study to simulate discharge for Selangor River. Rainfall and streamflow data from January 2005 to December 2015 is used in this study. The available three rainfall stations and one streamflow station in Selangor River catchment area were used for simulation process. Data of maps and hydrological data from SRTM and DID were collected and analyzed for model input. HEC-HMS is used to develop the hydrological network scheme for the Selangor Basin and simulated flow discharge is obtained based on available rainfall data. Clark Unit Hydrograph method was used in simulation process. Then, calibrations processes were done to fit the simulated streamflow against the local streamflow measurement data. From the result obtained, Clark Unit hydrograph method is applicable in estimating flow discharge in ungauged Selangor catchment through projection of calibrated discharge -simulation based one available data. Then statistical error analysis take part to ensure there is no error for simulated and observed data. RMSE and NSE indicated that the model predictions are as accurate as the mean of the observed data. It shows that the simulated models were fit with the observed data and proves that the HECHMS is suitable to predict and analyze rainfall-runoff relationship in Selangor River Basin.